Monoamine structure and its effect on fully reacted substructures to synergistically toughen epoxy amine networks via topological control - Nguyen Thao Phan; Houlei Gan; David Szmalko; Claudia Creighton; Cara M. Doherty; Durga Acharya; Daniel J. Eyckens; Russell J. Varley (Chemical Engineering Journal, 2026)

Host identity shapes Endozoicomonas composition in coral microbiomes across depths and marine protected areas at Little Cayman Island - Madelaine L. Brown; Andrew J. Maritan; Gretchen Goodbody-Gringley; Matthew L. Doherty; Alex D. Chequer; Frank J. Stewart; Zoe A. Pratte (Coral Reefs, 2026)
The bacterial genus Endozoicomonas is prevalent and abundant in the microbiome of many corals, but the combination of environmental and host factors shaping its distribution remains uncertain. In this study, we used 16S rRNA gene sequencing to examine the distribution of Endozoicomonas across hard ( Porites astreoides , Montastraea cavernosa , Agaricia spp.) and soft coral ( Muricea spp., Gorgoniidae, Cladiellidae, Malacalcyonacea) microbiomes across a depth gradient from shallow (4.5 m) to upper mesophotic zones (36.6 m) at four sites around the Little Cayman Island, including two marine protected areas. Endozoicomonas was abundant across all coral microbiomes, with soft corals exhibiting near-total dominance (relative abundance range 0.1–99%, median 55.3%) by this genus and notable abundances (range 0–96%, median 22.2%) in hard corals. Endozoicomonas composition was strongly structured by coral host identity across sites and depths, with each coral type harboring two to four unique Endozoicomonas amplicon sequence variants. Site and depth also contributed to Endozoicomonas abundance in soft and hard corals, respectively, where relative abundances were highest at unprotected sites in soft corals and in shallow to mid photic zones in hard corals. These findings suggest that Endozoicomonas abundance is shaped by both coral host identity and local environmental conditions.

Quantitative assessment of knowledge gaps and research priorities for understanding and managing population irruptions of crown-of-thorns starfish (Acanthaster cf. solaris) on Australia’s Great Barrier Reef - Morgan S. Pratchett; Peter C. Doll; Christopher Cvitanovic; Shaun K. Wilson; Russell C. Babcock; Yves-Marie Bozec; Deborah Burn; Maria Byrne; Carolina Castro-Sanguino; Carla C. M. Chen; Scott A. Condie; Zara-Louise Cowan; et al. (Coral Reefs, 2026)
Despite extensive research on the western Pacific crown-of-thorns starfish (CoTS; Acanthaster cf. solaris ), especially from Australia’s Great Barrier Reef (GBR), there are persistent knowledge gaps that constrain understanding and management. Given renewed population irruptions of CoTS on the GBR, alongside escalating climate impacts and direct anthropogenic pressures, a quantitative assessment of knowledge gaps was undertaken to identify research priorities and guide future efforts. In this study, 27 experts independently scored 206 research questions across seven Themes and 39 topics, based on four different criteria ( Knowledge gap , Feasibility , Urgency , and Applicability ). These questions were ultimately rationalized into 170 distinct questions, with scores aggregated across merged questions. Management was the highest scoring Theme for Urgency , Applicability , and overall. All but six of the 20 top-ranked questions were from the Management Theme and mainly related to Culling and/ or Monitoring. Most questions (158 out of 170) also scored highly for Feasibility , suggesting that there are existing methods and technical capability available to advance the extensive and diverse range of research questions that were posed, if resources were made available. This quantitative assessment provides guidance on the prioritization of potential research that could improve management of CoTS populations to improve coral protection outcomes on the GBR. This study also suggests that there are limited constraints to undertaking necessary research to address many of the persistent knowledge gaps relating to CoTS.

Exercise-induced bronchodilation is not impacted by beta-adrenergic receptor blockade in males or females - Connor J. Doherty; Benjamin P. Thompson; Paige J. Rynne; Jou-Chung Chang; Sarah A. Angus; Armando J. Aguero; Sean L. Gartner; Paolo Dominelli (European Journal of Applied Physiology, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Transcriptomic analysis reveals time-of-day-specific genes and gene regulatory networks in response to chilling stress in sorghum - Kanjana Laosuntisuk; Amaranatha Vennapusa; Impa M. Somayanda; S. V. Krishna Jagadish; Colleen J. Doherty (Plant Physiology Reports, 2025)
Sorghum is a versatile crop with many uses, ranging from human consumption to biofuel production. In the U.S., sorghum experiences heat stress during flowering in the summer. Several strategies have been developed to reduce yield loss caused by heat stress. One of the most reliable strategies is ‘heat escape’, in which early-season planting shifts the crop’s reproductive phase to occur before heat stress exposure. However, this heat escape strategy is limited due to sorghum’s sensitivity to early-season chilling. In sorghum, early-season chilling stress negatively affects seed germination, emergence, and seedling vigor. Candidate chilling-tolerant genes in sorghum have been proposed, but the molecular mechanisms of the candidate genes in chilling stress response have not been well established. We hypothesized that many transcriptional responses critical for sorghum’s response to low temperature have been missed by not examining gene expression at multiple times throughout the day. Here, we investigated the effect of chilling stress and time of day on transcriptional responses using 3′ RNA-Seq. We found that time-of-day gated gene expression in response to chilling stress results in various transcriptional response patterns, each with unique biological processes. Weighted gene correlation network analysis (WGCNA) identified modules of transcripts that are specifically responsive to nighttime chilling. Candidate regulatory transcription factors (TFs) of the chilling stress response in sorghum were identified through gene regulatory network analysis. Our results demonstrate that the time of day samples are collected substantially affects our understanding of chilling tolerance, and suggest that a full capture of the network of chilling stress responses requires an examination of multiple times of day. By profiling transcription across different times of day under chilling conditions, we identify regulatory programs that can be leveraged to expand early-planting windows.

Alignment between Duplex Sequencing and transgenic rodent mutation assay data in the assessment of in vivo NDMA-induced mutagenesis - Anne L. Ashford; Daniela Nachmanson; John W. Wills; Jacob E. Higgins; Thomas H. Smith; Kevin C. Vavra; Farah A. Dahalan; Jonathan Howe; Joanne M. Elloway; Jesse J. Salk; Ann Doherty; Anthony M. Lynch (Archives of Toxicology, 2025)

Spatial footprint of maritime vessels in the waters of a fast-growing coastal megalopolis - Stephen D.J. Lang; Philip D. Doherty; Brendan J. Godley; Shing Yip Lee; Felix Leung; Manmohan D. Sharma; Kristian Metcalfe (Marine Policy, 2025)

Effects of illumination and pot design on catch and bycatch when targeting northern shrimp (Pandalus borealis) using white LED PotLights - Thomas W. Horton; Robert Enever; Brendan J. Godley; Pete Kibel; Donald Malone; Duncan McAndrew; Philip D. Doherty (Ocean & Coastal Management, 2025)

Numerical Analysis of Triaxial Tests for Interpreting Sample Stiffness with Existing Measurement Systems - W. Du; B. M. Lehane; J. P. Doherty; Z. Wang (Geotechnical and Geological Engineering, 2025)
This paper presents the first systematic numerical study employing a realistic elasto-plastic non-linear soil model to examine factors affecting the measurement of soil stiffness at low to intermediate strains in the triaxial apparatus. The study is motivated by the development of new image-based measurement techniques for triaxial testing. The results from numerical simulations are presented that quantify the influence on sample stiffness determination of three important features common to all triaxial tests, namely: the misalignment of the loading direction and the top of the sample (and indirectly bedding errors), the use of fixed or free load cell connections and the effect of system compliance. The analyses compare data obtained using four different instrumentation systems employed for axial strain measurement with overall predicted deformations and elemental response of a typical sand sample. The paper highlights some of the significant errors that can occur in standard triaxial tests and makes recommendations to assist more accurate determinations of sample stiffness. It is also shown numerically that, despite sample and test imperfections, the common approach of averaging data from at least two strain gauges located on a triaxial sample’s middle third can lead to reasonable inference of a soil’s elemental Youngs modulus.

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Field measurements of steelhead trout Oncorhynchus mykiss distribution, swimming behavior and response to water current exposure in a sea cage - M. Chambers; M. Doherty; M. Coogan; C. Rillahan; J. DeCew; P. Lader; W.H. Howell (Aquaculture, 2025)

Outcome measurement instruments used to measure diet-related outcomes in infancy: A scoping review - Karen Matvienko-Sikar; Moira Duffy; Eibhlín Looney; Reindolf Anokye; Catherine S. Birken; Vicki Brown; Darren Dahly; Ann S. Doherty; Dimity Dutch; Rebecca Golley; Brittany J. Johnson; Patricia Leahy-Warren; et al. (Appetite, 2025)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

‘Megafire’—You May Not Like It, But You Cannot Avoid It - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2025)
Aim The term ‘megafire’ is increasingly used to describe large fires worldwide. We proposed a size‐based definition of megafire—fires exceeding 10,000 ha arising from single or multiple related ignition events. A recent perspective in Global Ecology and Biogeography argues against a size‐based definition of megafire and suggest that the term is too emotive for scientific use. We highlight that many scientific terms originate from common terms. These terms are often defined once they enter the scientific lexicon, enhancing both scientific understanding and public communication. We argue that standardised definitions facilitate better prediction, preparation, and management of fire events. Location Worldwide. Time Period 2022–2023. Methods We conducted an updated structured review of the term ‘megafire’ and its use and definition in the peer‐reviewed scientific literature, collating definitions and descriptions and identifying the criteria frequently invoked to define the term. Results We demonstrate an increase in the use of ‘megafire’ in the scientific literature since our original definition in 2022, with many studies adopting the > 10,000 ha size‐based criterion. Main Conclusions We contend that abandoning the term is neither practical, possible, nor beneficial. Instead, consistent usage underpinned by clear definitions is essential. Adopting a clear, size‐based definition of megafire strengthens clarity and comparability across research and management practices globally. Precision in terminology is crucial for advancing research, improving communication, and informing effective fire management and policy.

Animal-borne sensors reveal high human impact on soundscapes near a critical sea turtle nesting beach - Francesco Garzon; Pierre Didier Agamboue; Jack A. Boyle; Philip D. Doherty; Angela Formia; Brendan J. Godley; Lucy A. Hawkes; David A. Mann; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Guy-Phillipe Sounguet; et al. (Biological Conservation, 2024)

Escaping the cohort of concern: in vitro experimental evidence supports non-mutagenicity of N-nitroso-hydrochlorothiazide - R. D. Gandhi; S. Hickert; Y. Hoevelmann; C. D. Mee; J. Schlingemann; A. Adams; A. Blanazs; S. Simon; J. Elloway; L. Rigger; A. Teasdale; C. V. Beaumont; et al. (Archives of Toxicology, 2024)

Ticks and lyme disease in natural areas: A segmentation analysis of visitor perceptions of risk and preferred communication strategies - Ryan M. Brady; Christopher J. Lemieux; Sean T. Doherty (Journal of Outdoor Recreation and Tourism, 2024)

Experimentally testing animal responses to prescribed fire size and severity - Tim S. Doherty; Daniel F. Bohórquez Fandiño; Darcy J. Watchorn; Sarah M. Legge; Chris R. Dickman (Conservation Biology, 2024)
Deserts are often highly biodiverse and provide important habitats for many threatened species. Fire is a dominant disturbance in deserts, and prescribed burning is increasingly being used by conservation managers and Indigenous peoples to mitigate the damaging effects of climate change, invasive plants, and land‐use change. The size, severity, and patchiness of fires can affect how animals respond to fire. However, there are almost no studies examining such burn characteristics in desert environments, which precludes the use of such information in conservation planning. Using a before‐after control‐impact approach with 20 sampling sites, we studied the outcomes of 10 prescribed burns of varying size (5–267 ha), severity, and patchiness to identify which variables best predicted changes in small mammal and reptile species richness and abundance. Three of the 13 species showed a clear response to fire. Captures increased for 2 species (1 mammal, 1 reptile) and decreased for 1 species (a reptile) as the proportional area burned around traps increased. Two other mammal species showed weaker positive responses to fire. Total burn size and burn patchiness were not influential predictors for any species. Changes in capture rates occurred only at sites with the largest and most severe burns. No fire‐related changes in capture rates were observed where fires were small and very patchy. Our results suggest that there may be thresholds of fire size or fire severity that trigger responses to fire, which has consequences for management programs underpinned by the patch mosaic burning paradigm. The prescribed burns we studied, which are typical in scale and intensity across many desert regions, facilitated the presence of some taxa and are unlikely to have widespread or persistent negative impacts on small mammal or reptile communities in this ecosystem provided that long unburned habitat harboring threatened species is protected.

Vertical trophic structure and niche partitioning of gelatinous predators in a pelagic food web: Insights from stable isotopes of siphonophores - Elizabeth D. Hetherington; Hilary G. Close; Steven H. D. Haddock; Alejandro Damian‐Serrano; Casey W. Dunn; Natalie J. Wallsgrove; Shannon C. Doherty; C. Anela Choy (Limnology and Oceanography, 2024)
Gelatinous zooplankton are increasingly recognized as key components of pelagic ecosystems, and there have been many recent insights into their ecology and roles in food webs. To examine the trophic ecology of siphonophores (Cnidaria, Hydrozoa), we used bulk (carbon and nitrogen) and compound‐specific (nitrogen) isotope analysis of individual amino acids (CSIA‐AA). We collected samples of 15 siphonophore genera using blue‐water diving, midwater trawls, and remotely operated vehicles in the California Current Ecosystem, from 0 to 3000 m. We examined the basal resources supporting siphonophore nutrition by comparing their isotope values to those of contemporaneously collected sinking and suspended particles (0–500 m). Stable isotope values provided novel insights into siphonophore trophic ecology, indicating considerable niche overlap between calycophoran and physonect siphonophores. However, there were clear relationships between siphonophore trophic positions and phylogeny, and the highest siphonophore trophic positions were restricted to physonects. Bulk and source amino acid nitrogen isotope (δ 15 N) values of siphonophores and suspended particles all increased significantly with increasing collection depth. In contrast, siphonophore trophic positions did not increase with increasing collection depth. This suggests that microbially reworked, deep, suspended particles with higher δ 15 N values than surface particles, likely indirectly support deep‐pelagic siphonophores. Siphonophores feed upon a range of prey, from small crustaceans to fishes, and we show that their measured trophic positions reflect this trophic diversity, spanning 1.5 trophic levels (range 2.4–4.0). Further, we demonstrate that CSIA‐AA can elucidate the feeding ecology of gelatinous zooplankton and distinguish between nutritional resources across vertical habitats. These findings improve our understanding of the functional roles of gelatinous zooplankton and energy flow through pelagic food webs.

Artificial refuges provide post-fire habitat for small vertebrates - Darcy J. Watchorn; Chris R. Dickman; Aaron Greenville; Barbara A. Wilson; Mark J. Garkaklis; Don A. Driscoll; Pat Hodgens; Dayna Hoadley; Heidi Groffen; Tim S. Doherty (Biological Conservation, 2024)

Ozone at Mace Head, Ireland from 1987 to 2021: Declining baselines, phase-out of European regional pollution, COVID-19 impacts - Richard G. Derwent; David D. Parrish; Alistair J. Manning; T. Gerard Spain; Peter G. Simmonds; Simon O'Doherty (Atmospheric Environment, 2024)

A nose for trouble: ecotoxicological implications for climate change and disease in Saiga antelope (S. t. tatarica) - S. T. Mullineaux; J. M. McKinley; N. J. Marks; R. Doherty; D. M. Scantlebury (Environmental Geochemistry and Health, 2024)
In recent decades, Saiga antelope ( Saiga t. tatarica ) mass die-offs have become more common. The mass die-off of 2015 in central Kazakhstan, recorded 140,000 individual deaths across multiple herds. Previously, research has shown atmospheric humidity, the bacterium Pasteurella multocida serotype B, and resultant haemorrhagic septicaemia, were the primary cause. However, other synergistic factors may have impacted this process. Here we use a multivariate compositional data analysis (CoDA) approach to assess what other factors may have been involved. We show a pollutant linkage mechanism where relative humidity and dewpoint temperature combine with environmental pollutants, potentially toxic elements (e.g., Hg, As), complex carbon compounds (e.g., Acetone, Toluene), and inorganic compounds (e.g., CHx, SO 2 ) which affected the Saiga during the calving season (start and peak) and at the onset of the mass die-off. We suggest a mechanism for this process. Upon arrival at their carving grounds, the Saiga experienced a sudden precipitation event, a spike in temperatures, and resultant high humidity occurs. The infectious bacterium P . multocida serotype B then spreads. Further, environmental pollutants contained within steppe soils are released to the air, forming localised smog events, these synergistically combine, and mass die-off occurs.

Using coral holes to explore the historical ecology of Guam’s coral reefs - Jonathan D. Cybulski; John M. Doherty; Carly LaRoche; Kelly Donovan Gutkowski; Zizhan Luo; Elizabeth J. Malloy; Laurel MacMillan; Laurie Raymundo; Kiho Kim (Coral Reefs, 2023)

High-frequency, continuous hydrogen observations at Mace Head, Ireland from 1994 to 2022: Baselines, pollution events and ‘missing’ sources - Richard G. Derwent; Peter G. Simmonds; Simon O'Doherty; Alistair J. Manning; T. Gerard Spain (Atmospheric Environment, 2023)

P16-33: Identifying and characterizing toxicity liabilities of pharmaceuticals using ToxProfiler: A blinded case study with the ITLF consortium - B. Ter Braak; L. Wolters; K. Elbertse; M. Beilmann; H. Boonen; A. Doherty; F. Van Goethem; P. Hewitt; J. Hornberg; J. Koch; S. Kusterman; J. Lyon; et al. (Toxicology Letters, 2023)

Cadmium reduces growth of male fetuses by impairing development of the placental vasculature and reducing expression of nutrient transporters - Danielle Kozlosky; Alexander Lu; Cathleen Doherty; Brian Buckley; Michael J. Goedken; Richard K. Miller; Emily S. Barrett; Lauren M. Aleksunes (Toxicology and Applied Pharmacology, 2023)

Integrated and data Science-informed seabed characterisation for optimised foundation design - M.P. O'Neill; A.L. Osuchowski; Y. Cai; M.F. Bransby; P.G. Watson; C. Gaudin; J. Doherty; E. Dalgaard; R. Ross (Ocean Engineering, 2023)

Estimating co‐extinction threats in terrestrial ecosystems - Seamus Doherty; Frédérik Saltré; John Llewelyn; Giovanni Strona; Stephen E. Williams; Corey J. A. Bradshaw (Global Change Biology, 2023)
The biosphere is changing rapidly due to human endeavour. Because ecological communities underlie networks of interacting species, changes that directly affect some species can have indirect effects on others. Accurate tools to predict these direct and indirect effects are therefore required to guide conservation strategies. However, most extinction‐risk studies only consider the direct effects of global change—such as predicting which species will breach their thermal limits under different warming scenarios—with predictions of trophic cascades and co‐extinction risks remaining mostly speculative. To predict the potential indirect effects of primary extinctions, data describing community interactions and network modelling can estimate how extinctions cascade through communities. While theoretical studies have demonstrated the usefulness of models in predicting how communities react to threats like climate change, few have applied such methods to real‐world communities. This gap partly reflects challenges in constructing trophic network models of real‐world food webs, highlighting the need to develop approaches for quantifying co‐extinction risk more accurately. We propose a framework for constructing ecological network models representing real‐world food webs in terrestrial ecosystems and subjecting these models to co‐extinction scenarios triggered by probable future environmental perturbations. Adopting our framework will improve estimates of how environmental perturbations affect whole ecological communities. Identifying species at risk of co‐extinction (or those that might trigger co‐extinctions) will also guide conservation interventions aiming to reduce the probability of co‐extinction cascades and additional species losses.

Meta‐analysis reveals impacts of disturbance on reptile and amphibian body condition - Kristina J. Macdonald; Don A. Driscoll; Kimberley J. Macdonald; Bronwyn Hradsky; Tim S. Doherty (Global Change Biology, 2023)
Ecosystem disturbance is increasing in extent, severity and frequency across the globe. To date, research has largely focussed on the impacts of disturbance on animal population size, extinction risk and species richness. However, individual responses, such as changes in body condition, can act as more sensitive metrics and may provide early warning signs of reduced fitness and population declines. We conducted the first global systematic review and meta‐analysis investigating the impacts of ecosystem disturbance on reptile and amphibian body condition. We collated 384 effect sizes representing 137 species from 133 studies. We tested how disturbance type, species traits, biome and taxon moderate the impacts of disturbance on body condition. We found an overall negative effect of disturbance on herpetofauna body condition (Hedges' g = −0.37, 95% CI: −0.57, −0.18). Disturbance type was an influential predictor of body condition response and all disturbance types had a negative mean effect. Drought, invasive species and agriculture had the largest effects. The impact of disturbance varied in strength and direction across biomes, with the largest negative effects found within Mediterranean and temperate biomes. In contrast, taxon, body size, habitat specialisation and conservation status were not influential predictors of disturbance effects. Our findings reveal the widespread effects of disturbance on herpetofauna body condition and highlight the potential role of individual‐level response metrics in enhancing wildlife monitoring. The use of individual response metrics alongside population and community metrics would deepen our understanding of disturbance impacts by revealing both early impacts and chronic effects within affected populations. This could enable early and more informed conservation management.

Combining exercise with cognitive training and vitamin D3 to improve functional brain connectivity (FBC) in older adults with mild cognitive impairment (MCI). Results from the SYNERGIC trial - Nick W. Bray; Frederico Pieruccini-Faria; Suzanne T. Witt; Robert Bartha; Timothy J. Doherty; Lindsay S. Nagamatsu; Quincy J. Almeida; Teresa Liu-Ambrose; Laura E. Middleton; Louis Bherer; Manuel Montero-Odasso (GeroScience, 2023)

Auxin–cytokinin interplay shapes root functionality under low-temperature stress - Manish Tiwari; Ritesh Kumar; Senthil Subramanian; Colleen J. Doherty; S.V. Krishna Jagadish (Trends in Plant Science, 2023)

Frailty and functional brain connectivity (FBC) in older adults with mild cognitive impairment (MCI): baseline results from the SYNERGIC Trial - Nick W. Bray; Frederico Pieruccini-Faria; Suzanne T. Witt; Kenneth Rockwood; Robert Bartha; Timothy J. Doherty; Lindsay S. Nagamatsu; Quincy J. Almeida; Teresa Liu-Ambrose; Laura E. Middleton; Louis Bherer; Manuel Montero-Odasso (GeroScience, 2023)

Warming and hypoxia reduce the performance and survival of northern bay scallops ( Argopecten irradians irradians ) amid a fishery collapse - Stephen J. Tomasetti; Brendan D. Hallinan; Stephen T. Tettelbach; Nils Volkenborn; Owen W. Doherty; Bassem Allam; Christopher J. Gobler (Global Change Biology, 2023)
Warming temperatures and diminishing dissolved oxygen (DO) concentrations are among the most pervasive drivers of global coastal change. While regions of the Northwest Atlantic Ocean are experiencing greater than average warming, the combined effects of thermal and hypoxic stress on marine life in this region are poorly understood. Populations of the northern bay scallop, Argopecten irradians irradians across the northeast United States have experienced severe declines in recent decades. This study used a combination of high‐resolution (~1 km) satellite‐based temperature records, long‐term temperature and DO records, field and laboratory experiments, and high‐frequency measures of scallop cardiac activity in an ecosystem setting to quantify decadal summer warming and assess the vulnerability of northern bay scallops to thermal and hypoxic stress across their geographic distribution. From 2003 to 2020, significant summer warming (up to ~0.2°C year −1 ) occurred across most of the bay scallop range. At a New York field site in 2020, all individuals perished during an 8‐day estuarine heatwave that coincided with severe diel‐cycling hypoxia. Yet at a Massachusetts site with comparable DO levels but lower daily mean temperatures, mortality was not observed. A 96‐h laboratory experiment recreating observed daily temperatures of 25 or 29°C, and normoxia or hypoxia (22.2% air saturation), revealed a 120‐fold increased likelihood of mortality in the 29°C‐hypoxic treatment compared with control conditions, with scallop clearance rates also reduced by 97%. Cardiac activity measurements during a field deployment indicated that low DO and elevated daily temperatures modulate oxygen consumption rates and likely impact aerobic scope. Collectively, these findings suggest that concomitant thermal and hypoxic stress can have detrimental effects on scallop physiology and survival and potentially disrupt entire fisheries. Recovery of hypoxic systems may benefit vulnerable fisheries under continued warming.

Contribution of household and personal care products to 1,4-dioxane contamination of drinking water - Anne-Cooper Doherty; Cheng-Shiuan Lee; Qingyu Meng; Yuko Sakano; Abigail E. Noble; Kelly A. Grant; Adrienne Esposito; Christopher J. Gobler; Arjun K. Venkatesan (Current Opinion in Environmental Science & Health, 2023)

Opportunistic camera surveys provide insight into discrete foraging behaviours in nurse sharks (Ginglymostoma cirratum) - Kristian J. Parton; Philip D. Doherty; Mark Parrish; Philip Shearer; Keith Myrick; Oliver N. Shipley; Austin J. Gallagher (Environmental Biology of Fishes, 2023)

Correction to: Near-term climate risks and solar radiation modification: a roadmap approach for physical sciences research - Kelly Wanser; Sarah J. Doherty; James W. Hurrell; Alex Wong (Climatic Change, 2022)

Near-term climate risks and sunlight reflection modification: a roadmap approach for physical sciences research - Kelly Wanser; Sarah J. Doherty; James W. Hurrell; Alex Wong (Climatic Change, 2022)
Current impacts and escalating risks of climate change require strong and decisive action to reduce greenhouse gas (GHG) emissions. They also highlight the urgency of research to enhance safety for human and natural systems, especially for those most vulnerable. This is reflected in two recent US National Academies of Science, Engineering, and Medicine studies that recommended a national focus on advancing our understanding of how to manage urgent current and future climate risks, and the study of approaches for increasing the reflection of sunlight from the atmosphere to reduce global warming, a process referred to as sunlight reflection modification (SRM). Here, we build on these recommendations by proposing a roadmap approach for the planning, coordination, and delivery of research to support a robust scientific assessment of SRM to reduce near-term climate risks in a defined timeframe. This approach is designed to support the evaluation of SRM as a possible rapid, temporary, additive measure to reduce catastrophic impacts from anthropogenic climate change, not as a substitute for aggressive GHG mitigation. Assessing SRM is proposed to be undertaken in the context of climate hazard risks through 2050, weighing the impacts associated with likely climate change trajectories against scenarios of possible SRM implementations. Provided that research is undertaken openly and that scientific resources are made widely available, the transparency of the process and the evidence generated would contribute to the democratization of information, participation by diverse stakeholders, more informed decision-making, and better opportunities for all people to weigh SRM options against climate change risks.

What do you mean, ‘megafire’? - Grant D. Linley; Chris J. Jolly; Tim S. Doherty; William L. Geary; Dolors Armenteras; Claire M. Belcher; Rebecca Bliege Bird; Andrea Duane; Michael‐Shawn Fletcher; Melisa A. Giorgis; Angie Haslem; Gavin M. Jones; et al. (Global Ecology and Biogeography, 2022)
Background ‘Megafire’ is an emerging concept commonly used to describe fires that are extreme in terms of size, behaviour, and/or impacts, but the term’s meaning remains ambiguous. Approach We sought to resolve ambiguity surrounding the meaning of ‘megafire’ by conducting a structured review of the use and definition of the term in several languages in the peer‐reviewed scientific literature. We collated definitions and descriptions of megafire and identified criteria frequently invoked to define megafire. We recorded the size and location of megafires and mapped them to reveal global variation in the size of fires described as megafires. Results We identified 109 studies that define the term ‘megafire’ or identify a megafire, with the term first appearing in the peer‐reviewed literature in 2005. Seventy‐one (~65%) of these studies attempted to describe or define the term. There was considerable variability in the criteria used to define megafire, although definitions of megafire based on fire size were most common. Megafire size thresholds varied geographically from > 100–100,000 ha, with fires > 10,000 ha the most common size threshold (41%, 18/44 studies). Definitions of megafire were most common from studies led by authors from North America (52%, 37/71). We recorded 137 instances from 84 studies where fires were reported as megafires, the vast majority (94%, 129/137) of which exceed 10,000 ha in size. Megafires occurred in a range of biomes, but were most frequently described in forested biomes (112/137, 82%), and usually described single ignition fires (59% 81/137). Conclusion As Earth’s climate and ecosystems change, it is important that scientists can communicate trends in the occurrence of larger and more extreme fires with clarity. To overcome ambiguity, we suggest a definition of megafire as fires > 10,000 ha arising from single or multiple related ignition events. We introduce two additional terms – gigafire (> 100,000 ha) and terafire (> 1,000,000 ha) – for fires of an even larger scale than megafires.

Effects of meteorological and land surface modeling uncertainty on errors in winegrape ET calculated with SIMS - Conor T. Doherty; Lee F. Johnson; John Volk; Meagan S. Mauter; Nicolas Bambach; Andrew J. McElrone; Joseph G. Alfieri; Lawrence E. Hipps; John H. Prueger; Sebastian J. Castro; Maria Mar Alsina; William P. Kustas; et al. (Irrigation Science, 2022)
Characterization of model errors is important when applying satellite-driven evapotranspiration (ET) models to water resource management problems. This study examines how uncertainty in meteorological forcing data and land surface modeling propagate through to errors in final ET data calculated using the Satellite Irrigation Management Support (SIMS) model, a computationally efficient ET model driven with satellite surface reflectance values. The model is applied to three instrumented winegrape vineyards over the 2017–2020 time period and the spatial and temporal variation in errors are analyzed. We illustrate how meteorological data inputs can introduce biases that vary in space and at seasonal timescales, but that can persist from year to year. We also observe that errors in SIMS estimates of land surface conductance can have a particularly strong dependence on time of year. Overall, meteorological inputs introduced RMSE of 0.33–0.65 mm/day (7–27%) across sites, while SIMS introduced RMSE of 0.55–0.83 mm/day (19–24%). The relative error contribution from meteorological inputs versus SIMS varied across sites; errors from SIMS were larger at one site, errors from meteorological inputs were larger at a second site, and the error contributions were of equal magnitude at the third site. The similar magnitude of error contributions is significant given that many satellite-driven ET models differ in their approaches to estimating land surface conductance, but often rely on similar or identical meteorological forcing data. The finding is particularly notable given that SIMS makes assumptions about the land surface (no soil evaporation or plant water stress) that do not always hold in practice. The results of this study show that improving SIMS by eliminating these assumptions would result in meteorological inputs dominating the error budget of the model on the whole. This finding underscores the need for further work on characterizing spatial uncertainty in the meteorological forcing of ET.

Microbiome assembly in thawing permafrost and its feedbacks to climate - Jessica G. Ernakovich; Robyn A. Barbato; Virginia I. Rich; Christina Schädel; Rebecca E. Hewitt; Stacey J. Doherty; Emily D. Whalen; Benjamin W. Abbott; Jiri Barta; Christina Biasi; Chris L. Chabot; Jenni Hultman; et al. (Global Change Biology, 2022)
The physical and chemical changes that accompany permafrost thaw directly influence the microbial communities that mediate the decomposition of formerly frozen organic matter, leading to uncertainty in permafrost–climate feedbacks. Although changes to microbial metabolism and community structure are documented following thaw, the generality of post‐thaw assembly patterns across permafrost soils of the world remains uncertain, limiting our ability to predict biogeochemistry and microbial community responses to climate change. Based on our review of the Arctic microbiome, permafrost microbiology, and community ecology, we propose that Assembly Theory provides a framework to better understand thaw‐mediated microbiome changes and the implications for community function and climate feedbacks. This framework posits that the prevalence of deterministic or stochastic processes indicates whether the community is well‐suited to thrive in changing environmental conditions. We predict that on a short timescale and following high‐disturbance thaw (e.g., thermokarst), stochasticity dominates post‐thaw microbiome assembly, suggesting that functional predictions will be aided by detailed information about the microbiome. At a longer timescale and lower‐intensity disturbance (e.g., active layer deepening), deterministic processes likely dominate, making environmental parameters sufficient for predicting function. We propose that the contribution of stochastic and deterministic processes to post‐thaw microbiome assembly depends on the characteristics of the thaw disturbance, as well as characteristics of the microbial community, such as the ecological and phylogenetic breadth of functional guilds, their functional redundancy, and biotic interactions. These propagate across space and time, potentially providing a means for predicting the microbial forcing of greenhouse gas feedbacks to global climate change.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Ethnicity, socioeconomic status, income inequality, and colorectal cancer outcomes: evidence from the 4C2 collaboration - Cathy J. Bradley; Amy Anderson-Mellies; Evelinn A. Borrayo; Jennifer Anne Doherty; Omar A. Escontrías; David O. Garcia; Shiraz I. Mishra; Andrew L. Sussman; Cynthia A. Thomson; David W. Wetter; Linda S. Cook (Cancer Causes & Control, 2022)

Animal mortality during fire - Chris J. Jolly; Chris R. Dickman; Tim S. Doherty; Lily M. van Eeden; William L. Geary; Sarah M. Legge; John C. Z. Woinarski; Dale G. Nimmo (Global Change Biology, 2022)
Earth's rapidly warming climate is propelling us towards an increasingly fire‐prone future. Currently, knowledge of the extent and characteristics of animal mortality rates during fire remains rudimentary, hindering our ability to predict how animal populations may be impacted in the future. To address this knowledge gap, we conducted a global systematic review of the direct effects of fire on animal mortality rates, based on studies that unequivocally determined the fate of animals during fire. From 31 studies spanning 1984–2020, we extracted data on the direct impacts of fire on the mortality of 31 species from 23 families. From these studies, there were 43 instances where direct effects were measured by reporting animal survival from pre‐ to post‐fire. Most studies were conducted in North America (52%) and Oceania (42%), focused largely on mammals (53%) and reptiles (30%), and reported mostly on animal survival in planned (82%) and/or low severity (70%) fires. We found no studies from Asia, Europe or South America. Although there were insufficient data to conduct a formal meta‐analysis, we tested the effect of fire type, fire severity, fire regime, animal body mass, ecological attributes and class on survival. Only fire severity affected animal mortality, with a higher proportion of animals being killed by high than low severity fires. Recent catastrophic fires across the globe have drawn attention to the plight of animals exposed to wildfire. Yet, our systematic review suggests that a relatively low proportion of animals (mean predicted mortality [95% CI] = 3% [1%–9%]) are killed during fire. However, our review also underscores how little we currently know about the direct effects of fire on animal mortality, and highlights the critical need to understand the effects of high severity fire on animal populations.

Exploring relationships between oxygen consumption and biologger‐derived estimates of heart rate in two warmwater piscivores - Claire L.J. Doherty; Aaron T. Fisk; Steven J. Cooke; Trevor E. Pitcher; Graham D. Raby (Journal of Fish Biology, 2022)
Estimating metabolic rate in wild, free‐swimming fish is inherently challenging. Here, we explored using surgically implanted heart rate biologgers to estimate metabolic rate in two warmwater piscivores, bowfin Amia calva (Linneaus 1766) and largemouth bass Micropterus salmoides (Lacepède 1802). Fish were surgically implanted with heart rate loggers, allowed to recover for 24 h, exposed to a netting and air exposure challenge, and then placed into respirometry chambers so that oxygen consumption rate ( Ṁ O2 ) could be measured in parallel to heart rate ( f H ) for a minimum of 20 h ( ca . 20 estimates of Ṁ O2 ). Heart rate across the duration of the experiment (at 19°C) was significantly higher in largemouth bass (mean ± s.d. , 45 ± 14 beats min −1 , range 18–86) than in bowfin (27 ± 9 bpm, range 16–98). Standard metabolic rate was also higher in largemouth bass (1.06 ± 0.19 mg O 2 kg −1 min −1 , range 0.46–1.36) than in bowfin (0.89 ± 0.17 mg O 2 kg −1 min −1 , range 0.61–1.28). There were weak relationships between f H and Ṁ O2 , with heart rate predicting 28% of the variation in oxygen consumption in bowfin and 23% in largemouth bass. The shape of the relationship differed somewhat between the two species, which is perhaps unsurprising given their profound differences in physiology and life history, illustrating the need to carry out species‐specific validations. Both species showed some potential for a role of f H in efforts to estimate field metabolic rates, although further validation experiments with a wider range of conditions ( e.g ., digestive states, swimming activity) would likely help improve the strength of the Ṁ O2 – f H relationship for use in field applications.

Evaluation of sex-based differences in airway size and the physiological implications - Leah M. Mann; Sarah A. Angus; Connor J. Doherty; Paolo B. Dominelli (European Journal of Applied Physiology, 2021)

Pre-diagnosis neutrophil-to-lymphocyte ratio and mortality in individuals who develop lung cancer - Laurie Grieshober; Stefan Graw; Matt J. Barnett; Gary E. Goodman; Chu Chen; Devin C. Koestler; Carmen J. Marsit; Jennifer A. Doherty (Cancer Causes & Control, 2021)
Purpose The neutrophil-to-lymphocyte ratio (NLR) is a marker of systemic inflammation that has been reported to be associated with survival after chronic disease diagnoses, including lung cancer. We hypothesized that the inflammatory profile reflected by pre-diagnosis NLR, rather than the well-studied pre-treatment NLR at diagnosis, may be associated with increased mortality after lung cancer is diagnosed in high-risk heavy smokers. Methods We examined associations between pre-diagnosis methylation-derived NLR (mdNLR) and lung cancer-specific and all-cause mortality in 279 non-small lung cancer (NSCLC) and 81 small cell lung cancer (SCLC) cases from the β-Carotene and Retinol Efficacy Trial (CARET). Cox proportional hazards models were adjusted for age, sex, smoking status, pack years, and time between blood draw and diagnosis, and stratified by stage of disease. Models were run separately by histotype. Results Among SCLC cases, those with pre-diagnosis mdNLR in the highest quartile had 2.5-fold increased mortality compared to those in the lowest quartile. For each unit increase in pre-diagnosis mdNLR, we observed 22–23% increased mortality (SCLC-specific hazard ratio [HR] = 1.23, 95% confidence interval [CI]: 1.02, 1.48; all-cause HR = 1.22, 95% CI 1.01, 1.46). SCLC associations were strongest for current smokers at blood draw (Interaction P s = 0.03). Increasing mdNLR was not associated with mortality among NSCLC overall, nor within adenocarcinoma ( N = 148) or squamous cell carcinoma ( N = 115) case groups. Conclusion Our findings suggest that increased mdNLR, representing a systemic inflammatory profile on average 4.5 years before a SCLC diagnosis, may be associated with mortality in heavy smokers who go on to develop SCLC but not NSCLC.

Physical activity in relation to circulating hormone concentrations in 117,100 men in UK Biobank - Eleanor L. Watts; Aurora Perez-Cornago; Aiden Doherty; Naomi E. Allen; Georgina K. Fensom; Sandar Tin Tin; Timothy J. Key; Ruth C. Travis (Cancer Causes & Control, 2021)
Purpose Physical activity may reduce the risk of some types of cancer in men. Biological mechanisms may involve changes in hormone concentrations; however, this relationship is not well established. Therefore, we aimed to investigate the associations of physical activity with circulating insulin-like growth factor-I (IGF-I), sex hormone-binding globulin (SHBG, which modifies sex hormone activity), and total and free testosterone concentrations, and the extent these associations might be mediated by body mass index (BMI). Methods Circulating concentrations of these hormones and anthropometric measurements and self-reported physical activity data were available for 117,100 healthy male UK Biobank participants at recruitment. Objectively measured accelerometer physical activity levels were also collected on average 5.7 years after recruitment in 28,000 men. Geometric means of hormone concentrations were estimated using multivariable-adjusted analysis of variance, with and without adjustment for BMI. Results The associations between physical activity and hormones were modest and similar for objectively measured (accelerometer) and self-reported physical activity. Compared to men with the lowest objectively measured physical activity, men with high physical activity levels had 14% and 8% higher concentrations of SHBG and total testosterone, respectively, and these differences were attenuated to 6% and 3% following adjustment for BMI. Conclusion Our results suggest that the associations of physical activity with the hormones investigated are, at most, modest; and following adjustment for BMI, the small associations with SHBG and total testosterone were largely attenuated. Therefore, it is unlikely that changes in these circulating hormones explain the associations of physical activity with risk of cancer either independently or via BMI.

Threats of illegal, unregulated, and unreported fishing to biodiversity and food security in the Republic of the Congo - Philip D. Doherty; Benoit C. Atsango; Gaston Ngassiki; Appolinaire Ngouembe; Nathalie Bréheret; Eva Chauvet; Brendan J. Godley; Lucie Machin; Baudelaire Dissondet Moundzoho; Richard J. Parnell; Kristian Metcalfe (Conservation Biology, 2021)
Illegal, unregulated, and unreported (IUU) fishing poses a major threat to effective management of marine resources, affecting biodiversity and communities dependent on these coastal resources. Spatiotemporal patterns of industrial fisheries in developing countries are often poorly understood, and global efforts to describe spatial patterns of fishing vessel activity are currently based on automatic identification system (AIS) data. However, AIS is often not a legal requirement on fishing vessels, likely resulting in underestimates of the scale and distribution of legal and illegal fishing activity, which could have significant ramifications for targeted enforcement efforts and the management of fisheries resources. To help address this knowledge gap, we analyzed 3 years of vessel monitoring system (VMS) data in partnership with the national fisheries department in the Republic of the Congo to describe the behavior of national and distant‐water industrial fleets operating in these waters. We found that the spatial footprint of the industrial fisheries fleet encompassed over one‐quarter of the Exclusive Economic Zone. On average, 73% of fishing activity took place on the continental shelf (waters shallower than 200 m). Our findings highlight that VMS is not acting as a deterrent or being effectively used as a proactive management tool. As much as 33% (13% on average) of fishing effort occurred in prohibited areas set aside to protect biodiversity, including artisanal fisheries resources, and the distant‐water fleet responsible for as much as 84% of this illegal activity. Given the growth in industrial and distant‐water fleets across the region, as well as low levels of management and enforcement, these findings highlight that there is an urgent need for the global community to help strengthen regional and national capacity to analyze national scale data sets if efforts to combat IUU fishing are to be effective.

Chronic kidney disease of unknown origin is associated with environmental urbanisation in Belfast, UK - Jennifer M. McKinley; Ute Mueller; Peter M. Atkinson; Ulrich Ofterdinger; Siobhan F. Cox; Rory Doherty; Damian Fogarty; J. J. Egozcue; V. Pawlowsky-Glahn (Environmental Geochemistry and Health, 2021)
Chronic kidney disease (CKD), a collective term for many causes of progressive renal failure, is increasing worldwide due to ageing, obesity and diabetes. However, these factors cannot explain the many environmental clusters of renal disease that are known to occur globally. This study uses data from the UK Renal Registry (UKRR) including CKD of uncertain aetiology (CKDu) to investigate environmental factors in Belfast, UK. Urbanisation has been reported to have an increasing impact on soils. Using an urban soil geochemistry database of elemental concentrations of potentially toxic elements (PTEs), we investigated the association of the standardised incidence rates (SIRs) of both CKD and CKD of uncertain aetiology (CKDu) with environmental factors (PTEs), controlling for social deprivation. A compositional data analysis approach was used through balances (a special class of log contrasts) to identify elemental balances associated with CKDu. A statistically significant relationship was observed between CKD with the social deprivation measures of employment, income and education (significance levels of 0.001, 0.01 and 0.001, respectively), which have been used as a proxy for socio-economic factors such as smoking. Using three alternative regression methods (linear, generalised linear and Tweedie models), the elemental balances of Cr/Ni and As/Mo were found to produce the largest correlation with CKDu. Geogenic and atmospheric pollution deposition, traffic and brake wear emissions have been cited as sources for these PTEs which have been linked to kidney damage. This research, thus, sheds light on the increasing global burden of CKD and, in particular, the environmental and anthropogenic factors that may be linked to CKDu, particularly environmental PTEs linked to urbanisation.

Use of Exposomic Methods Incorporating Sensors in Environmental Epidemiology - Brett T. Doherty; Jeremy P. Koelmel; Elizabeth Z. Lin; Megan E. Romano; Krystal J. Godri Pollitt (Current Environmental Health Reports, 2021)

Multiple-endpoint in vitro carcinogenicity test in human cell line TK6 distinguishes carcinogens from non-carcinogens and highlights mechanisms of action - Katherine E. Chapman; Eleanor C. Wilde; Fiona M. Chapman; Jatin R. Verma; Ume-Kulsoom Shah; Leanne M. Stannard; Anna L. Seager; James A. Tonkin; M. Rowan Brown; Ann T. Doherty; George E. Johnson; Shareen H. Doak; et al. (Archives of Toxicology, 2021)
Current in vitro genotoxicity tests can produce misleading positive results, indicating an inability to effectively predict a compound’s subsequent carcinogenic potential in vivo. Such oversensitivity can incur unnecessary in vivo tests to further investigate positive in vitro results, supporting the need to improve in vitro tests to better inform risk assessment. It is increasingly acknowledged that more informative in vitro tests using multiple endpoints may support the correct identification of carcinogenic potential. The present study, therefore, employed a holistic, multiple-endpoint approach using low doses of selected carcinogens and non-carcinogens (0.001–770 µM) to assess whether these chemicals caused perturbations in molecular and cellular endpoints relating to the Hallmarks of Cancer. Endpoints included micronucleus induction, alterations in gene expression, cell cycle dynamics, cell morphology and bioenergetics in the human lymphoblastoid cell line TK6. Carcinogens ochratoxin A and oestradiol produced greater Integrated Signature of Carcinogenicity scores for the combined endpoints than the “misleading” in vitro positive compounds, quercetin, 2,4-dichlorophenol and quinacrine dihydrochloride and toxic non-carcinogens, caffeine, cycloheximide and phenformin HCl. This study provides compelling evidence that carcinogens can successfully be distinguished from non-carcinogens using a holistic in vitro test system. Avoidance of misleading in vitro outcomes could lead to the reduction and replacement of animals in carcinogenicity testing.

Spatial Ecology of Sub-Adult Green Turtles in Coastal Waters of the Turks and Caicos Islands: Implications for Conservation Management - Philip D. Doherty; Annette Cameron Broderick; Brendan John Godley; K. A. Hart; Q. Phillips; A. Sanghera; Thomas B. Stringell; J. T. Walker; Peter Bradley Richardson (Frontiers in Marine Science, 2020)

Reptile responses to anthropogenic habitat modification: A global meta‐analysis - Tim S. Doherty; Sara Balouch; Kristian Bell; Thomas J. Burns; Anat Feldman; Charles Fist; Timothy F. Garvey; Tim S. Jessop; Shai Meiri; Don A. Driscoll (Global Ecology and Biogeography, 2020)
Aim The aim was to determine how reptile populations respond to anthropogenic habitat modification and determine whether species traits and environmental factors influence such responses. Location Global. Time period 1981–2018. Major taxa studied Squamata. Methods We compiled a database of 56 studies reporting how habitat modification affects reptile abundance and calculated standardized mean differences in abundance (Hedges’ g ). We used Bayesian meta‐analytical models to test whether responses to habitat modification depended on body size, clutch size, reproductive mode, habitat specialization, range size, disturbance type, vegetation type, temperature and precipitation. Results Based on 815 effect sizes from 376 species, we found an overall negative effect of habitat modification on reptile abundance (mean Hedges’ g = −0.43, 95% credible intervals = −0.61 to −0.26). Reptile abundance was, on average, one‐third lower in modified compared with unmodified habitats. Small range sizes and small clutch sizes were associated with more negative responses to habitat modification, although the responses were weak and the credible intervals overlapped zero. We detected no effects of body size, habitat specialization, reproductive mode (egg‐laying or live‐bearing), temperature or precipitation. Some families exhibited more negative responses than others, although overall there was no phylogenetic signal in the data. Mining had the most negative impacts on reptile abundance, followed by agriculture, grazing, plantations and patch size reduction, whereas the mean effect of logging was neutral. Main conclusions Habitat modification is a key cause of reptile population declines, although there is variability in responses both within and between species, families and vegetation types. The effect of disturbance type appeared to be related to the intensity of habitat modification. Ongoing development of environmentally sustainable practices that ameliorate anthropogenic impacts is urgently needed to prevent declines in reptile populations.

Assessing the Effects of Banana Pingers as a Bycatch Mitigation Device for Harbour Porpoises (Phocoena phocoena) - Lucy C. M. Omeyer; Philip D. Doherty; Sarah Dolman; Robert Enever; Allan Reese; Nicholas Tregenza; Ruth Williams; Brendan J. Godley (Frontiers in Marine Science, 2020)

Systems biology analysis identifies molecular determinants of chemotherapy-induced diarrhoea - Andreas U. Lindner; Alexa J. Resler; Steven Carberry; Kasia Oficjalska; Orna Bacon; Chun Seng Lee; Abdurehman Choudhry; John P. Burke; Kieran Sheahan; Mattia Cremona; Bryan T Hennessy; Deborah McNamara; et al. (Journal of Molecular Medicine, 2020)

Only a matter of time: the impact of daily and seasonal rhythms on phytochemicals - Donna J. Liebelt; Juliette T. Jordan; Colleen J. Doherty (Phytochemistry Reviews, 2019)

A critique of 'countryside biogeography' as a guide to research in human‐dominated landscapes - Don A. Driscoll; Sara Balouch; Thomas J. Burns; Tim F. Garvey; Tricia Wevill; Kaori Yokochi; Tim S. Doherty (Journal of Biogeography, 2019)
Proliferation of redundant terms in ecology and conservation slows progress and creates confusion. ‘Countryside biogeography’ has been promoted as a new framework for conservation in production landscapes, so may offer a replacement for other concepts used by landscape ecologists. We conducted a systematic review to assess whether the 'countryside biogeography' concept provides a distinctive framing for conservation in human‐dominated landscapes relative to existing concepts. We reviewed 147 papers referring to countryside biogeography and 81 papers that did not. These papers were divided into categories representing three levels of use of countryside biogeography concepts (strong, weak, cited only) and two categories that did not use countryside biogeography at all but used similar concepts including fragmentation and matrix. We revealed few distinctions among groups of papers. Countryside biogeography papers made more frequent use of the terms 'ecosystem services', 'intensification' and 'land sparing' compared with non‐countryside biogeography papers. Papers that did not refer to countryside biogeography sampled production areas (e.g. farms) less often, and this related to their focus on habitat specialist species for which patch‐matrix assumptions were reasonable. Countryside biogeography offers a conceptual wrapper rather than a distinctive framework for advancing research in human‐modified landscapes. This and similar wrappers such as ‘conservation biogeography’ and ‘agricultural biogeography’ risk creating confusion among new researchers, and can prevent clear communication about research. To improve communication, we recommend using the suite of well‐established terms already applied to conservation in human‐modified landscapes rather than through an interceding conceptual wrapper.

Using Cumulative Impact Mapping to Prioritize Marine Conservation Efforts in Equatorial Guinea - Brittany T. Trew; Hedley S. Grantham; Christian Barrientos; Tim Collins; Philip D. Doherty; Angela Formia; Brendan J. Godley; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Dominic Tilley; Matthew J. Witt; et al. (Frontiers in Marine Science, 2019)

Seasonal changes in basking shark vertical space use in the north-east Atlantic - P. D. Doherty; J. M. Baxter; B. J. Godley; R. T. Graham; G. Hall; J. Hall; L. A. Hawkes; S. M. Henderson; L. Johnson; C. Speedie; M. J. Witt (Marine Biology, 2019)
Mobile marine species can exhibit vast movements both horizontally and vertically. Spatial analysis of vertical movements may help improve an understanding of the processes that influence space use. Previously, vertical space use of basking sharks ( Cetorhinus maximus ) in the north-east Atlantic described movements largely within waters of the continental shelf during summer and autumn months, with few records of detailed vertical behaviour during winter. We use archival satellite telemetry data from 32 basking sharks (12 females, 6 males, and 14 of unknown sex measuring 4–5 m ( n = 6), 5–6 m ( n = 10), 6–7 m ( n = 7), 7–8 m ( n = 8), and 8–9 m ( n = 1) estimated total length) tracked over 4 years (2012–2015). The satellite tags provided depth and temperature data for a cumulative 4489 days (mean 140 ± 97 days per shark, range 10–292 days) to describe vertical space use and thermal range of basking sharks in the north-east Atlantic. Basking sharks exhibit seasonality in vertical space use, revealing repeated ‘yo-yo’ movement behaviour with periods of occupancy at depths greater than 1000 m in late winter/early spring. Describing seasonal vertical space use in marine megavertebrates can increase knowledge of movements throughout their environment including physiological and morphological constraints to movement, nutrient transfer, and overlap with anthropogenic threats to inform future conservation strategies.

Novel transcriptional responses to heat revealed by turning up the heat at night - Dmitry O. Grinevich; Jigar S. Desai; Kevin P. Stroup; Jiaqi Duan; Erin Slabaugh; Colleen J. Doherty (Plant Molecular Biology, 2019)

Stratigraphic model of the Quaternary sediments of the Western Irish Sea Mud Belt from core, geotechnical and acoustic data - Mark Coughlan; Andrew J. Wheeler; Boris Dorschel; Mike Long; Paul Doherty; Tobias Mörz (Geo-Marine Letters, 2019)

Joint exposure to smoking, excessive weight, and physical inactivity and survival of ovarian cancer patients, evidence from the Ovarian Cancer Association Consortium - Albina N. Minlikeeva; Rikki Cannioto; Allan Jensen; Susanne K. Kjaer; Susan J. Jordan; Brenda Diergaarde; J. Brian Szender; Kunle Odunsi; Hani Almohanna; Paul Mayor; Kirsten Starbuck; Emese Zsiros; et al. (Cancer Causes & Control, 2019)

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

Correction to: Acute phenylalanine/tyrosine depletion of phasic dopamine in the rat brain - Tatiana A. Shnitko; Sarah C. Taylor; Sierra J. Stringfield; Shannon L. Zandy; Roberto U. Cofresí; James M. Doherty; William B. Lynch; Charlotte A. Boettiger; Rueben A. Gonzales; Donita L. Robinson (Psychopharmacology, 2018)

Insolation and disturbance history drive biocrust biodiversity in Western Montana rangelands - Rebecca A. Durham; Kyle D. Doherty; Anita J. Antoninka; Philip W. Ramsey; Matthew A. Bowker (Plant and Soil, 2018)

Biocrust moss populations differ in growth rates, stress response, and microbial associates - Kyle D. Doherty; Matthew A. Bowker; Anita J. Antoninka; Nancy C. Johnson; Troy E. Wood (Plant and Soil, 2018)

Migration and survival of Atlantic salmon Salmo salar smolts in a large natural lake - Richard J. Kennedy; Robert Rosell; Michael Millane; Dennis Doherty; Michelle Allen (Journal of Fish Biology, 2018)
An investigation with acoustic telemetry of the passage of Salmo salar smolts through a large natural lake found heavy mortality occurred at the river‐to‐lake confluences (mean 31.2% km −1 ), but was lower in the main body of the lake (mean 2.4% km −1 ). Predation was a significant pressure on emigrating smolts as tagged pike Esox lucius aggregated at river‐to‐lake confluences during the peak of the smolt run. Tagged smolts mainly emmigrated into the lake in the late evening after dusk, possibly as a predator‐avoidance behaviour.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

A novel, integrated in vitro carcinogenicity test to identify genotoxic and non-genotoxic carcinogens using human lymphoblastoid cells - Eleanor C. Wilde; Katherine E. Chapman; Leanne M. Stannard; Anna L. Seager; Katja Brüsehafer; Ume-Kulsoom Shah; James A. Tonkin; M. Rowan Brown; Jatin R. Verma; Ann T. Doherty; George E. Johnson; Shareen H. Doak; et al. (Archives of Toxicology, 2018)

Informing Marine Protected Area Designation and Management for Nesting Olive Ridley Sea Turtles Using Satellite Tracking - Tiffany M. Dawson; Angela Formia; Pierre D. Agamboué; Georges M. Asseko; François Boussamba; Floriane Cardiec; Emmanuel Chartrain; Philip D. Doherty; J. Michael Fay; Brendan J. Godley; Francis Lambert; Brice D. Koumba Mabert; et al. (Frontiers in Marine Science, 2017)

Ecosystem Responses to Fire: Identifying Cross-taxa Contrasts and Complementarities to Inform Management Strategies - Tim S. Doherty; Eddie J. B. van Etten; Robert A. Davis; Chris Knuckey; James Q. Radford; Sarah A. Dalgleish (Ecosystems, 2017)

History of hypertension, heart disease, and diabetes and ovarian cancer patient survival: evidence from the ovarian cancer association consortium - Albina N. Minlikeeva; Jo L. Freudenheim; Rikki A. Cannioto; J. Brian Szender; Kevin H. Eng; Francesmary Modugno; Roberta B. Ness; Michael J. LaMonte; Grace Friel; Brahm H. Segal; Kunle Odunsi; Paul Mayor; et al. (Cancer Causes & Control, 2017)

Molecular detection of kobuviruses in livestock in Northern Ireland and the Republic of Ireland - P. J. Collins; Michael J. McMenamy; Julie McClintock; Paula Lagan-Tregaskis; Lorna McCabe; Simon Doherty; Helen O’Shea; Michael Welsh; John McKillen (Archives of Virology, 2017)

Conserving long unburnt vegetation is important for bird species, guilds and diversity - Robert A. Davis; Tim S. Doherty; Eddie J.B. van Etten; James Q. Radford; Floyd Holmes; Chris Knuckey; Belinda J. Davis (Biodiversity and Conservation, 2016)

Large‐scale, multidirectional larval connectivity among coral reef fish populations in the Great Barrier Reef Marine Park - David H. Williamson; Hugo B. Harrison; Glenn R. Almany; Michael L. Berumen; Michael Bode; Mary C. Bonin; Severine Choukroun; Peter J. Doherty; Ashley J. Frisch; Pablo Saenz‐Agudelo; Geoffrey P. Jones (Molecular Ecology, 2016)
Larval dispersal is the key process by which populations of most marine fishes and invertebrates are connected and replenished. Advances in larval tagging and genetics have enhanced our capacity to track larval dispersal, assess scales of population connectivity, and quantify larval exchange among no‐take marine reserves and fished areas. Recent studies have found that reserves can be a significant source of recruits for populations up to 40 km away, but the scale and direction of larval connectivity across larger seascapes remain unknown. Here, we apply genetic parentage analysis to investigate larval dispersal patterns for two exploited coral reef groupers ( Plectropomus maculatus and Plectropomus leopardus ) within and among three clusters of reefs separated by 60–220 km within the Great Barrier Reef Marine Park, Australia. A total of 69 juvenile P. maculatus and 17 juvenile P. leopardus (representing 6% and 9% of the total juveniles sampled, respectively) were genetically assigned to parent individuals on reefs within the study area. We identified both short‐distance larval dispersal within regions (200 m to 50 km) and long‐distance, multidirectional dispersal of up to ~250 km among regions. Dispersal strength declined significantly with distance, with best‐fit dispersal kernels estimating median dispersal distances of ~110 km for P. maculatus and ~190 km for P. leopardus . Larval exchange among reefs demonstrates that established reserves form a highly connected network and contribute larvae for the replenishment of fished reefs at multiple spatial scales. Our findings highlight the potential for long‐distance dispersal in an important group of reef fishes, and provide further evidence that effectively protected reserves can yield recruitment and sustainability benefits for exploited fish populations.

Adaptation services and pathways for the management of temperate montane forests under transformational climate change - Matthew J. Colloff; Michael D. Doherty; Sandra Lavorel; Michael Dunlop; Russell M. Wise; Suzanne M. Prober (Climatic Change, 2016)

Fish viruses make dsRNA in fish cells: characterization of dsRNA production in rainbow trout ( Oncorhynchus mykiss ) cells infected with viral haemorrhagic septicaemia virus, chum salmon reovirus and frog virus 3 - L Doherty; S J Poynter; A Aloufi; S J DeWitte‐Orr (Journal of Fish Diseases, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Acute phenylalanine/tyrosine depletion of phasic dopamine in the rat brain - Tatiana A. Shnitko; Sarah C. Taylor; Sierra J. Stringfield; Shannon L. Zandy; Roberto U. Cofresí; James M. Doherty; William B. Lynch; Charlotte A. Boettiger; Rueben A. Gonzales; Donita L. Robinson (Psychopharmacology, 2016)

Large genomic rearrangements in the familial breast and ovarian cancer gene BRCA1 are associated with an increased frequency of high risk features - Paul A. James; Sarah Sawyer; Samantha Boyle; Mary-Anne Young; Serguei Kovalenko; Rebecca Doherty; Joanne McKinley; Kathryn Alsop; Victoria Beshay; Marion Harris; Stephen Fox; Geoffrey J. Lindeman; et al. (Familial Cancer, 2015)

A continental‐scale analysis of feral cat diet in Australia - Tim S. Doherty; Robert A. Davis; Eddie J. B. van Etten; Dave Algar; Neil Collier; Chris R. Dickman; Glenn Edwards; Pip Masters; Russell Palmer; Sue Robinson (Journal of Biogeography, 2015)
Aim Reducing the impacts of feral cats ( Felis catus ) is a priority for conservation managers across the globe, and success in achieving this aim requires a detailed understanding of the species’ ecology across a broad spectrum of climatic and environmental conditions. We reviewed the diet of the feral cat across Australia and on Australian territorial islands, seeking to identify biogeographical patterns in dietary composition and diversity, and use the results to consider how feral cats may best be managed. Location Australia and its territorial islands. Methods Using 49 published and unpublished data sets, we modelled trophic diversity and the consumption of eight food groups against latitude, longitude, mean temperature, precipitation, environmental productivity and climate‐habitat regions. Results We recorded 400 vertebrate species that feral cats feed on or kill in Australia, including 28 IUCN Red List species. We found evidence of continental‐scale prey‐switching from rabbits to small mammals, previously recorded only at the local scale. The consumption of arthropods, reptiles, rabbits, rodents and medium‐sized native mammals varied with different combinations of latitude, longitude, mean annual precipitation, temperature and environmental productivity. The frequency of rodents and dasyurids in cats’ diets increased as rabbit consumption decreased. Main conclusions The feral cat is an opportunistic, generalist carnivore that consumes a diverse suite of vertebrate prey across Australia. It uses a facultative feeding strategy, feeding mainly on rabbits when they are available, but switching to other food groups when they are not. Control programmes aimed at culling rabbits could potentially decrease the availability of a preferred food source for cats and then lead to greater predation pressure on native mammals. The interplay between cat diet and prey species diversity at a continental scale is complex, and thus cat management is likely to be necessary and most effective at the local landscape level.

Light-absorbing particles in snow and ice: Measurement and modeling of climatic and hydrological impact - Yun Qian; Teppei J. Yasunari; Sarah J. Doherty; Mark G. Flanner; William K. M. Lau; Jing Ming; Hailong Wang; Mo Wang; Stephen G. Warren; Rudong Zhang (Advances in Atmospheric Sciences, 2015)

Ecological mechanisms underpinning climate adaptation services - Sandra Lavorel; Matthew J. Colloff; Sue Mcintyre; Michael D. Doherty; Helen T. Murphy; Daniel J. Metcalfe; Michael Dunlop; Richard J. Williams; Russell M. Wise; Kristen J. Williams (Global Change Biology, 2015)
Ecosystem services are typically valued for their immediate material or cultural benefits to human wellbeing, supported by regulating and supporting services. Under climate change, with more frequent stresses and novel shocks, 'climate adaptation services', are defined as the benefits to people from increased social ability to respond to change, provided by the capability of ecosystems to moderate and adapt to climate change and variability. They broaden the ecosystem services framework to assist decision makers in planning for an uncertain future with new choices and options. We present a generic framework for operationalising the adaptation services concept. Four steps guide the identification of intrinsic ecological mechanisms that facilitate the maintenance and emergence of ecosystem services during periods of change, and so materialise as adaptation services. We applied this framework for four contrasted Australian ecosystems. Comparative analyses enabled by the operational framework suggest that adaptation services that emerge during trajectories of ecological change are supported by common mechanisms: vegetation structural diversity, the role of keystone species or functional groups, response diversity and landscape connectivity, which underpin the persistence of function and the reassembly of ecological communities under severe climate change and variability. Such understanding should guide ecosystem management towards adaptation planning.

Changes in Pesticide Occurrence in Suburban Surface Waters in Massachusetts, USA, 1999–2010 - Hotze Wijnja; Jeffery J. Doherty; Saida A. Safie (Bulletin of Environmental Contamination and Toxicology, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Cigarette smoking and risk of ovarian cancer: a pooled analysis of 21 case–control studies - Mette T. Faber; Susanne K. Kjær; Christian Dehlendorff; Jenny Chang-Claude; Klaus K. Andersen; Estrid Høgdall; Penelope M. Webb; Susan J. Jordan; Mary Anne Rossing; Jennifer A. Doherty; Galina Lurie; Pamela J. Thompson; et al. (Cancer Causes & Control, 2013)

Attenuated effects of experimenter-administered heroin in adolescent vs. adult male rats: physical withdrawal and locomotor sensitization - James M. Doherty; Kyle J. Frantz (Psychopharmacology, 2013)

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

Breast-feeding and risk of epithelial ovarian cancer - S. J. Jordan; K. L. Cushing-Haugen; K. G. Wicklund; J. A. Doherty; M. A. Rossing (Cancer Causes & Control, 2012)

Delineation of the molecular mechanism for disulfide stress-induced aluminium toxicity - Ming J. Wu; Patricia A. Murphy; Patrick J. O’Doherty; Stephen Mieruszynski; Mark Jones; Cindy Kersaitis; Peter J. Rogers; Trevor D. Bailey; Vincent J. Higgins (BioMetals, 2012)

Heroin self-administration and reinstatement of heroin-seeking in adolescent vs. adult male rats - James M. Doherty; Kyle J. Frantz (Psychopharmacology, 2012)

The origins of neuromuscular fatigue post-stroke - S. Knorr; T. D. Ivanova; T. J. Doherty; J. A. Campbell; S. J. Garland (Experimental Brain Research, 2011)

Biomaterial-Based Vaccine Induces Regression of Established Intracranial Glioma in Rats - Omar A. Ali; Ed Doherty; William J. Bell; Tracie Fradet; Jebecka Hudak; Marie-Therese Laliberte; David J. Mooney; Dwaine F. Emerich (Pharmaceutical Research, 2011)

Population structure and genetic diversity of greater sage-grouse (Centrocercus urophasianus) in fragmented landscapes at the northern edge of their range - Krista L. Bush; Christopher K. Dyte; Brendan J. Moynahan; Cameron L. Aldridge; Heather S. Sauls; Angela M. Battazzo; Brett L. Walker; Kevin E. Doherty; Jason Tack; John Carlson; Dale Eslinger; Joel Nicholson; et al. (Conservation Genetics, 2011)

Chromosome 15q24-25.1 variants, diet, and lung cancer susceptibility in cigarette smokers - Lori C. Sakoda; Melissa M. Loomis; Jennifer A. Doherty; Marian L. Neuhouser; Matt J. Barnett; Mark D. Thornquist; Noel S. Weiss; Gary E. Goodman; Chu Chen (Cancer Causes & Control, 2011)

Cohorts and consortia conference: a summary report (Banff, Canada, June 17–19, 2009) - Paolo Boffetta; Graham A. Colditz; John D. Potter; Laurence Kolonel; Paula J. Robson; Reza Malekzadeh; Daniela Seminara; Ellen L. Goode; Keun-Young Yoo; Paul Demers; Richard Gallagher; Ross Prentice; et al. (Cancer Causes & Control, 2011)

Pressure Filtration of Australian Bagasse Pulp - Thomas J. Rainey; William O. S. Doherty; D. Mark Martinez; Richard J. Brown; Neil A. Kelson (Transport in Porous Media, 2011)

Respiratory epithelial cells in innate immunity to influenza virus infection - Catherine J. Sanders; Peter C. Doherty; Paul G. Thomas (Cell and Tissue Research, 2011)

Iron intake and markers of iron status and risk of Barrett’s esophagus and esophageal adenocarcinoma - Mark G. O’Doherty; Christian C. Abnet; Liam J. Murray; Jayne V. Woodside; Lesley A. Anderson; John D. Brockman; Marie M. Cantwell (Cancer Causes & Control, 2010)

Determinants of Water Connection Type and Ownership of Water-Using Appliances in Ireland - Sean Lyons; Joe O’Doherty; Richard S. J. Tol (Water Resources Management, 2010)

Maximizing resources to study an uncommon cancer: E2C2—Epidemiology of Endometrial Cancer Consortium - Sara H. Olson; Chu Chen; Immaculata De Vivo; Jennifer A. Doherty; Virginia Hartmuller; Pamela L. Horn-Ross; James V. Lacey; Shannon M. Lynch; Leah Sansbury; V. Wendy Setiawan; Leo J. Schouten; Xiao Ou Shu (Cancer Causes & Control, 2009)

Potential Mortality Effects of Off-Highway Vehicles on the Flat-Tailed Horned Lizard (Phrynosoma mcallii): A Manipulative Experiment - Tyler J. Grant; Paul F. Doherty (Environmental Management, 2009)

Factors affecting Sciomyzidae (Diptera) across a transect at Skealoghan Turlough (Co. Mayo, Ireland) - Christopher D. Williams; James Moran; Owen Doherty; Rory J. Mc Donnell; Michael J. Gormally; Lloyd V. Knutson; Jean-Claude Vala (Aquatic Ecology, 2009)

Physical map of two tammar wallaby chromosomes: A strategy for mapping in non-model mammals - Janine E. Deakin; Edda Koina; Paul D. Waters; Ruth Doherty; Vidushi S. Patel; Margaret L. Delbridge; Bianca Dobson; James Fong; Yanqiu Hu; Cecilia van den Hurk; Andrew J. Pask; Geoff Shaw; et al. (Chromosome Research, 2008)

Radiative forcing from surface NO x emissions: spatial and seasonal variations - R. G. Derwent; D. S. Stevenson; R. M. Doherty; W. J. Collins; M. G. Sanderson; C. E. Johnson (Climatic Change, 2008)

Linkage mapping of the locus for inherited ovine arthrogryposis (IOA) to sheep Chromosome 5 - Angela M. Murphy; David E. MacHugh; Stephen D.E. Park; Erik Scraggs; Chris S. Haley; David J. Lynn; Maurice P. Boland; Michael L. Doherty (Mammalian Genome, 2007)

Turbulent mixing and mesoscale distributions of late‐stage fish larvae on the NW Shelf of Western Australia - M. G. MEEKAN; J. H. CARLETON; C. R. STEINBERG; A. D. MCKINNON; R. BRINKMAN; P. J. DOHERTY; A. HALFORD; S. DUGGAN; L. MASON (Fisheries Oceanography, 2006)
Light traps were deployed to describe vertical and cross‐shelf distributions of late‐stage larval fishes during five cruises in each of the 1997/98 and 1998/99 summers in the region of the Gulf of Exmouth on the southern North West Shelf of Western Australia. At each light trap station on a cross‐shelf transect we measured water temperature, salinity and chlorophyll a and used vertical plankton tows to estimate zooplankton biomass and copepod abundance. Current meters were deployed on moorings near the transect and the data used to model flows and mixing on the NW Shelf and in the Gulf. The majority of reef, pelagic and baitfish larvae (81, 83 and 66% respectively) were collected at only two stations that marked the boundary between stratified waters offshore and well‐mixed water within the Gulf. Most baitfishes (primarily Spratelloides spp.) were captured by traps deployed near the seabed, while reef fishes (mostly pomacentrids, lethrinids and siganids) and pelagic species (mostly scombrids and carangids) were captured in traps deployed near surface. Catch composition varied between summers with 64% of baitfishes collected in the first summer, while the majority of reef and pelagic fishes (81 and 80% respectively) were captured in the second summer. Modelling of circulation showed that the velocity of tidal currents was enhanced by constriction of flow between NW Cape and South Muiron Island and by shallowing of the shelf. Flood‐tide intrusions of water allowed the thermocline to move up the continental shelf, upwelling cool nutrient‐rich water that was then mixed throughout the entire water column at stations in the mouth of the Gulf. This upwelling and mixing resulted in higher chlorophyll a concentrations and copepod abundances either as a result of local in situ growth or advection/aggregation processes, and may account for the great abundances of late‐stage fish larvae in the mouth of the Gulf.

Matrix Gla protein and osteopontin genetic associations with coronary artery calcification and bone density: the CARDIA study - Brent C. Taylor; Pamela J. Schreiner; Terence M. Doherty; Myriam Fornage; J. Jeffrey Carr; Steve Sidney (Human Genetics, 2005)

Space weather effects of October?November 2003 - Patricia Doherty; Anthea J. Coster; William Murtagh (GPS Solutions, 2004)

The GPS ionospheric working group - Anthea J. Coster; Patricia Doherty (GPS Solutions, 2004)

AGAGE Observations of Methyl Bromide and Methyl Chloride at Mace Head, Ireland, and Cape Grim, Tasmania, 1998–2001 - P. G. Simmonds; R. G. Derwent; A. J. Manning; P. J. Fraser; P. B. Krummel; S. O'Doherty; R. G. Prinn; D. M. Cunnold; B. R. Miller; H. J. Wang; D. B. Ryall; L. W. Porter; et al. (Journal of Atmospheric Chemistry, 2004)

Subcutaneous Administration of a Recombinant Vaccinia Virus Vaccine Expressing Multiple Envelopes of HIV-1 - K. S. Slobod; T. D. Lockey; N. Howlett; R. V. Srinivas; S. D. Rencher; P. J. Freiden; P. C. Doherty; J. L. Hurwitz (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Toxicity Assessment of a Former Manufactured Gas Plant - A. S. Ferguson; R. Doherty; M. J. Larkin; R. M. Kalin; V. Irvine; U. S. Ofterdinger (Bulletin of Environmental Contamination and Toxicology, 2003)

Regional Sources of Methyl Chloride, Chloroform and Dichloromethane Identified from AGAGE Observations at Cape Grim, Tasmania, 1998–2000 - M. L. Cox; G. A. Sturrock; P. J. Fraser; S. T. Siems; P. B. Krummel; S. O'Doherty (Journal of Atmospheric Chemistry, 2003)

Second primary tumors in patients with upper aerodigestive tract cancers: joint effects of smoking and alcohol (United States) - Kim-Anh Do; Marcella M. Johnson; Dorota A. Doherty; J. Jack Lee; Xi Feng Wu; Qiong Dong; Waun K. Hong; Fadlo R. Khuri; Karen K. Fu; Margaret R. Spitz (Cancer Causes & Control, 2003)

Diel drift behaviour of fish eggs and larvae, in particular barbel, Barbus barbus (L.), in an English chalk stream - G. H. COPP; H. FAULKNER; S. DOHERTY; M. S. WATKINS; J. MAJECKI (Fisheries Management and Ecology, 2002)
To estimate the potential loss of fish larvae to downstream stretches, the downstream drift behaviour of fish eggs and larvae, in particular barbel, Barbus barbus (L.), was examined in the River Lee, a small, nutrient‐rich chalk stream in England, using drift nets over nine consecutive 24‐h periods in June 1993 at one location and over ten 24‐h periods, once a week for 10 weeks from May to July 1995 at a location slightly more upstream. The density of drifting fish larvae was not correlated with river discharge in 1993 or 1995. A clear diel pattern was found in the drift of fish eggs and larvae, with barbel being a predominant species. Almost all fish larvae drifted at night both in 1993 and 1995, but the drift of eggs in 1995 occurred regardless of luminosity, although most eggs drifted during the day and at dawn. The highest densities of drifting fish larvae (in particular barbel) were found in the nets set in the highest water velocities, with the opposite pattern observed for fish eggs, suggesting either active response to the water current or shape‐related differences in the drift behaviour of passive particles.

Zooplankton community structure and water flow in the lee of Helix Reef (Great Barrier Reef, Australia) - Carleton J.; Brinkman R.; Doherty P. (Marine Biology, 2001)

Emergy Evaluation of Reforestation Alternatives in Puerto Rico - Howard T. Odum; Steven J. Doherty; Frederick N. Scatena; Pushker A. Kharecha (Forest Science, 2000)
Six alternative ways of reforesting degraded lands in Puerto Rico were evaluated using emergy (spelled with an “m”). Emergy and its economic equivalent, emdollars, put the contributions of environmental work and human services on a comparable basis. This article shows the emergy method for evaluating forest contributions to public benefit and its use to select alternatives for reforestation. Emdollar values were compared for six scenarios for reforestation of degraded land in Puerto Rico: (1) the natural succession within or adjacent to mature forest; (2) reforestation from the spread of the exotic tree siris (Albizia lebbek); (3) reforestation with plantations of siris and mahogany for harvest; (4) reforestation by leaving plantations unharvested; (5) direct planting of seedlings of many species; and (6) starting patches of forest by massive transfer of topsoil, seed bank, and roots. After energy systems diagrams were made for each reforestation alternative, data were assembled and evaluation tables prepared that estimated the emergy required for: (1) canopy closure and (2) developing species complexity if left unharvested. To explain the method, detailed calculations were included for one of the alternatives, exotic Albizia lebbek plantation on 11 yr harvest cycle.All alternatives generated net public benefit (emdollar yield ratios 4.2 to 24.3). The emdollar value of a closed canopy developed in 10 to 20 yr ranged from 20,000 to 48,000 em$ /ha, whereas the economic costs were $1200 to $9700. For complex forest development in 25 to 60 yr, values ranged from 63,000 to 118,000 em$ /ha, much higher than economic costs of $4000 to $12,000/ha. Highest public benefit per dollar cost came from succession (24.7 em$/$) and exotic colonization (19.1 em$/$). Highest potential monetary returns were from exotic spread (15.1 $/$) and plantations (17.9 and 14.5 $/$). Stand quality after 60 yr, as measured by the transformity (emergy/energy), was largest in mahogany plantation (6.4 × 10 4 sej/J) and succession forest (3.9 × 104 sej/J). FOR. SCI. 46(4):521–530.

Dual X-ray absorptiometry detects disease- and treatment-related alterations of bone density in prostate cancer patients - Gillian L. Smith; Alan P. Doherty; Linda M. Banks; Jane Dutton; Iain W. Hanham; Timothy J. Christmas; Richard J. Epstein (Clinical & Experimental Metastasis, 2000)

Fully coupled climate/dynamical vegetation model simulations over Northern Africa during the mid-Holocene - R. Doherty; J. Kutzbach; J. Foley; D. Pollard (Climate Dynamics, 2000)

Hydroxyl Radical Concentrations Estimated from Measurements of Trichloroethylene during the EASE/ACSOE Campaign at Mace Head, Ireland during July 1996 - R. G. Derwent; N. Carslaw; P. G. Simmonds; M. Bassford; S. O'Doherty; D. B. Ryall; M. J. Pilling; A. C. Lewis; J. B. McQuaid (Journal of Atmospheric Chemistry, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Acute Toxicity of Potassium to the Adult Zebra Mussel Dreissena polymorpha - P. J. Wildridge; R. G. Werner; F. G. Doherty; E. F. Neuhauser (Archives of Environmental Contamination and Toxicology, 1998)

Tropical zooplankton in the highly-enclosed lagoon of Taiaro Atoll (Tuamotu Archipelago, French Polynesia) - J. H. Carleton; P. J. Doherty (Coral Reefs, 1998)

Objectives and background to the 1994 Franco-Australian expedition to Taiaro Atoll (Tuamotu Archipelago, French Polynesia) - R. Galzin; S. Planes; M. Adjeroud; C. Chauvet; P. J. Doherty; J. Poupin (Coral Reefs, 1998)

Replenishment of fish populations in the enclosed lagoon of Taiaro Atoll: (Tuamotu Archipelago, French Polynesia) evidence from eggs and larvae - J. M. Leis; T. Trnski; P. J. Doherty; V. Dufour (Coral Reefs, 1998)

Genetic relationships of the colour morphs of Acanthochromis polyacanthus (Pomacentridae) on the northern Great Barrier Reef - S. Planes; P. J. Doherty (Marine Biology, 1997)

Geochemistry of Tertiary tholeiites and picrites from Qeqertarssuaq (Disko Island) and Nuussuaq, West Greenland with implications for the mineral potential of comagmatic intrusions - Peter C. Lightfoot; Christopher J. Hawkesworth; Kevin Olshefsky; Tony Green; Will Doherty; Reid R. Keays (Contributions to Mineralogy and Petrology, 1997)